A perspective on magnetic core–shell carriers for responsive and targeted drug delivery systems - Albinali KE (Dove Medical Press, 2019)
Kholoud E Albinali,1 Moustafa M Zagho,1 Yonghui Deng,2 Ahmed A Elzatahry1 1Materials Science and Technology Program, College of Arts and Sciences, Qatar University, Doha, Qatar; 2Department of Chemistry, State Key Laboratory of Molecular Engineering of Polymers, Shanghai Key Laboratory of Molecular Catalysis and Innovative Materials, iChEM, Fudan University, Shanghai, People’s Republic of China Abstract: Magnetic core–shell nanocarriers have been attracting growing interest owing to their physicochemical and structural properties. The main principles of magnetic nanoparticles (MNPs) are localized treatment and stability under the effect of external magnetic fields. Furthermore, these MNPs can be coated or functionalized to gain a responsive property to a specific trigger, such as pH, heat, or even enzymes. Current investigations have been focused on the employment of this concept in cancer therapies. The evaluation of magnetic core–shell materials includes their magnetization properties, toxicity, and efficacy in drug uptake and release. This review discusses some categories of magnetic core–shell drug carriers based on Fe2O3 and Fe3O4 as the core, and different shells such as poly(lactic-co-glycolic acid), poly(vinylpyrrolidone), chitosan, silica, calcium silicate, metal, and lipids. In addition, the review addresses their recent potential applications for cancer treatment. Keywords: magnetic, mesoporous, core–shell, drug carriers, active targeting, passive targeting, controlled release, targeted cancer treatment